Factors Predicting Infection Prevention Behaviors among Caregivers of Children with Cancer Undergoing Chemotherapy - Klaisuban, Thatchkorn; Srichantaranit, Arunrat; Payakkaraung, Sudaporn (Nursing Science Journal of Thailand, 2024)
Purpose: The objective of this study was to assess the predictive power of health literacy, family support, and home environment on the infection prevention behaviors of caregivers of children with cancer undergoing chemotherapy. Design: Predictive correlational research. Methods: The study consisted of 80 caregivers of children with cancer, aged 1-15 years, all types of cancer at every state of treatment, who were followed up both inpatient and outpatient units at two tertiary hospitals in Bangkok. Convenience sampling was used to select the caregivers being the primary caregivers of the children while at home, aged 18-59 years, and able to communicate Thai language. Data were collected by using 5 questionnaires including 1) Demographic Data Questionnaire, 2) The Infection Prevention Behaviors Questionnaire, 3) The Health Literacy Questionnaire, 4) The Family Support Questionnaire, and 5) The Home Environment Questionnaire. The data were analyzed using descriptive statistics and stepwise multiple regression. Main findings: The results revealed that overall prevention infection behaviors were high ( = 116, SD = 11.69). The mean score of health literacy ( = 91.95, SD = 7.02) family support ( = 66.18, SD = 9.08) and home environment ( = 14.04, SD = 1.36) were also high. Health literacy was the only factor that could predict infection preventive behaviors ( = 0.30, t = 2.77, p < .01). Conclusion and recommendations: The caregivers’ infection prevention behaviors were influenced by their level of health literacy. Consequently, it is imperative for nurses and healthcare professionals to thoroughly assess the health literacy of caregivers. Then provide support by implementing interventions designed to enhance health literacy in order to improve understanding and application of infection prevention knowledge. These interventions should provide additional channels to access to knowledge, including the preparation of fruits and vegetables, as well as oral assessment and oral hygiene to prevent infections in children with cancer undergoing chemotherapy.